2020
DOI: 10.1177/1937586720912546
|View full text |Cite
|
Sign up to set email alerts
|

Safe and Supportive Neurorehabilitation Environments: Results of a Structured Observation of Physical Features Across Two Rehabilitation Facilities

Abstract: Objective: This research aimed to identify the extent to which physical features of two neurorehabilitation units appeared to support positive patient experience and recovery. Background: Neurorehabilitation inpatient facilities must be focused on safety management and efficiency of care, as well as being supportive of the patient experience. While occupational safety and risk management is paramount, the supportive nature of the physical setting for inpatient neurorehabilitation following spinal cord injury o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The findings of the current study correspond with those of Colley et al [33], who stated that growing research demonstrates the potential for healthcare environments to support recovery and participation following illness or injury, impacting a range of outcomes. They referred to the Internal Classification of Functioning, Disability and Health (ICF) developed by the WHO, which identifies environmental aspects as a core component of quality healthcare [33].…”
Section: A Core Component Of Quality Healthcaresupporting
confidence: 89%
“…The findings of the current study correspond with those of Colley et al [33], who stated that growing research demonstrates the potential for healthcare environments to support recovery and participation following illness or injury, impacting a range of outcomes. They referred to the Internal Classification of Functioning, Disability and Health (ICF) developed by the WHO, which identifies environmental aspects as a core component of quality healthcare [33].…”
Section: A Core Component Of Quality Healthcaresupporting
confidence: 89%
“…For example, the methodology could test the impact of engaging participants in woodwork or woodcraft activities, with the aim of developing furniture for the environment, or gardening activities with the aim of improving the natural environment, on the immediate feelings of inpatients and their perspectives of the physical environment. The proposed approach fills a methodological void in research around patient perspectives of hospital or healthcare environments, which have largely investigated inpatient and/or staff perspectives (Douglas & Douglas, 2004; Kotzer et al, 2011; Xuan et al, 2021) or researcher observations of patient use (Colley & Zeeman, 2020). Such research has been valuable and highlighted domains which support (i) health service provision, (ii) promote patient safety, and (iii) are associated with patient health and well-being outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is worthwhile to note that findings around the value of artwork are mixed, as research has also confirmed that restorative outcomes are best achieved for patients when their room does not include artwork (Gao & Zhang, 2020). Neurorehabilitation unit physical design understandably prioritizes hazard management, while giving less emphasis on promoting psychosocial health (Colley & Zeeman, 2020). Progressing robust research investigating the impact of including artwork throughout health facilities on the health and well-being of inpatients is a worthwhile endeavor.…”
mentioning
confidence: 99%
“…A recent study on users' perspectives in three rehabilitation centres foregrounds four key aspects through which the built environment contributes to patients' well-being: the importance of choice in activities and spaces, access to outside areas, opportunities for socialisation, and a ward configuration that aligns with the model of care [9]. Studies about the built environment in relation to patients' physical activity point at its potential to support or hinder rehabilitation [10,11]. A comparison between an old and new rehabilitation facility for stroke patients indicates that patients in single rooms with a faraway communal area, spend more time in their room, are less active, and have fewer interactions with staff and relatives than those in multi-bed rooms [12].…”
Section: Introductionmentioning
confidence: 99%